An Equilibrium Model of the Market for Bitcoin Mining - Julien Prat; Benjamin Walter (Center for Economic Studies and ifo Institute (CESifo), 2018)
We propose a model which uses the Bitcoin/US dollar exchange rate to predict the computing power of the Bitcoin network. We show that free entry places an upper-bound on mining revenues and we devise a structural framework to measure its value. Calibrating the model's parameters allows us to accurately forecast the evolution of the network computing power over time. We establish the accuracy of the model through out-of-sample tests and investigation of the entry rule.
Keywords: D41; L10; 330; Bitcoin; blockchain; miners; industry dynamics